Commutative domains of elementary divisors and some properties of their elements - Shchedrik, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study commutative domains of elementary divisors from the viewpoint of investigation of the structure of invertible matrices that reduce a given matrix to the diagonal form. Some properties of elements of these domains are indicated. We establish conditions, close to the stable-rank conditions, under which a commutative Bezout domain is a domain of ´ elementary divisors.